How HIV/AIDS scale-up has impacted on non- HIV priority services in Zambia - Brugha Ruairí; Simbaya Joseph; Walsh Aisling; Dicker Patrick; Ndubani Phillimon (BMC, 2010)
Abstract Background Much of the debate as to whether or not the scaling up of HIV service delivery in Africa benefits non-HIV priority services has focused on the use of nationally aggregated data. This paper analyses and presents routine health facility record data to show trend correlations across priority services. Methods Review of district office and health facility client records for 39 health facilities in three districts of Zambia, covering four consecutive years (2004-07). Intra-facility analyses were conducted, service and coverage trends assessed and rank correlations between services measured to compare service trends within facilities. Results VCT, ART and PMTCT client numbers and coverage levels increased rapidly. There were some strong positive correlations in trends within facilities between reproductive health services (family planning and antenatal care) and ART and PMTCT, with Spearman rank correlations ranging from 0.33 to 0.83. Childhood immunisation coverage also increased. Stock-outs of important drugs for non-HIV priority services were significantly more frequent than were stock-outs of antiretroviral drugs. Conclusions The analysis shows scale-up in reproductive health service numbers in the same facilities where HIV services were scaling up. While district childhood immunisations increased overall, this did not necessarily occur in facility catchment areas where HIV service scale-up occurred. The paper demonstrates an approach for comparing correlation trends across different services, using routine health facility information. Larger samples and explanatory studies are needed to understand the client, facility and health systems factors that contribute to positive and negative synergies between priority services.